Early Delirium Assessment for Hospitalized Older People in Indonesia: A Systematic Review - Saifullah, Azam David; Chen, Ching-Min (Nurse Media Journal of Nursing, 2016)
Background: Due to the increasing risk of getting co-morbidity and frailty, older people tend to be prone to hospitalization. Hospitalization in older people brings many adverse effects. Moreover, when these elderly get delirium, the mortality and morbidity will increase. The risk of getting deterioration and worsening condition because of delirium would also increase. In fact, delirium assessment is not a high priority in taking care older people during hospitalization because the focus of care is treating the disease.Delirium screening as an early recognition of delirium in the hospitalized elderly inIndonesia remains unreported and even do not well evaluated. Therefore, delirium as a preventable problem or causing problems remains unrecognized.Purpose: This paper aims to review the current evidence of early assessment of delirium in hospitalized older people.Methods: A systematic review was conducted from four databases yielding to 4 articles which met the inclusion and exclusion criteria.Results: There are four focuses on the result, namely delirium screening tools, patient characteristics, identified early delirium assessment, and outcomes affected by early delirium assessment. Confusion Assessment Method (CAM) was used as the delirium screening tool in the hospital. Establishing the care team involving many disciplines will give a better way to improve the integrated care and collaborative care.Conclusion: Performing CAM integrated into comprehensive geriatric assessment can be the most important thing to be undertaken when looking after the hospitalized elderly.